KALIMAT LUAS DALAM TALK SHOW KICK ANDY EPISODE KISAH SUKSES WANITA TERKUAT INDONESIA DI METRO TV - Dia, Eva Eri (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
The syntactic study of compound sentence used in the talk show Kick Andy for the Success Story of the Strongest Indonesian Women on Metro TV. This is as the object of research. The discussion raised by the researcher relates to compound sentences, namely grammatical relationship on compond sentences and grammatical relationship on complex sentences.The method used in this research is descriptive qualitative method. The reason the researcher uses descriptive qualitative methods is to describe objectively about the compound sentences and complex sentences. The data source used in this research is the talk show Kick Andy for the Success Story of the Strongest Indonesian Women on Metro TV and the data analyzed in this study are compound and complex sentences.The results of the study found the form of compound sentences using conjunctions of equivalent namely KI1 + but (tapi) + KI2, KI1 + and (dan) + KI2, KI1 + but (tetapi) + KI2 and KI1 + then(lalu) + KI2. The forms of complex sentence are found using conjunctions of unequal, KI1 + because (karena)+ KB, KI1 + which (yang)+ KB, and KI1 + that(bahwa)+ KB.